2016
DOI: 10.1152/jn.00074.2016
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency neural activity predicts word parsing in ambiguous speech streams

Abstract: Kösem A, Basirat A, Azizi L, van Wassenhove V. High-frequency neural activity predicts word parsing in ambiguous speech streams. J Neurophysiol 116: 2497-2512, 2016. First published September 7, 2016 doi:10.1152/jn.00074.2016.-During speech listening, the brain parses a continuous acoustic stream of information into computational units (e.g., syllables or words) necessary for speech comprehension. Recent neuroscientific hypotheses have proposed that neural oscillations contribute to speech parsing, but whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 102 publications
5
45
5
Order By: Relevance
“…After the chunk structure is parsed, the listener could synchronize their attention and predictions to the sequence. Previous studies have suggested that entrained neural oscillations may reflect both sequence parsing (Ding et al, 2016;Kösem et al, 2016;Meyer et al, 2016;Wang et al, 2017;Meyer and Gumbert, 2018) and temporal attention/prediction (Morillon and Baillet, 2017;Jin et al, 2018;Rimmele et al, 2018), and could causally modulate speech perception (Kösem et al, 2018;Riecke et al, 2018;Zoefel et al, 2018). The current results cannot distinguish which chunk-related process drives the chunk-rate response.…”
Section: Rule-based Chunking Hypothesiscontrasting
confidence: 84%
“…After the chunk structure is parsed, the listener could synchronize their attention and predictions to the sequence. Previous studies have suggested that entrained neural oscillations may reflect both sequence parsing (Ding et al, 2016;Kösem et al, 2016;Meyer et al, 2016;Wang et al, 2017;Meyer and Gumbert, 2018) and temporal attention/prediction (Morillon and Baillet, 2017;Jin et al, 2018;Rimmele et al, 2018), and could causally modulate speech perception (Kösem et al, 2018;Riecke et al, 2018;Zoefel et al, 2018). The current results cannot distinguish which chunk-related process drives the chunk-rate response.…”
Section: Rule-based Chunking Hypothesiscontrasting
confidence: 84%
“…The envelope of the audio signals was estimated by using a filter bank that models the passage of the signal through the cochlea . − Coherence between the speech envelope and neural activity in each voxel of both ROIs was obtained in the 0.5−10 Hz frequency band with 0.5 Hz frequency resolution . The average coherence value of all voxels in LAC and RAC was calculated for each participant, condition, and frequency bin.…”
Section: Methodsmentioning
confidence: 99%
“…Broadly speaking, this could be either acoustic features or higher-level language information (20,21). Recent work suggests that the different neural oscillatory markers link to distinct aspects of speech perception: theta entrainment underlies speech sound analysis (22)(23)(24) while delta oscillations reflect higher-level linguistic processing, such as semantic and syntactic processing (15,25).…”
Section: Introductionmentioning
confidence: 99%